Ø¯ÙˆØ± ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ØØ§Ø¯Ø«Ø© Ù„ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… ÙÙŠ Ù‚Ø³Ù… ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø¬Ø§Ù…Ø¹Ø© Ù‡Ø§Ø´Ù… Ø£Ø´Ø¹Ø±ÙŠ ØªØ¨ÙˆØ¦Ø±Ù†Ø¬ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ - Muhammad Fatihuddin; M. Burhanuddin Ubaidillah (Program Studi Pendidikan Bahasa Arab, 2020)
In muhadatsah’s study there is a problem that students usually experience as maharah kalam, because not all are able to express it properly. Sometimes, also do not have confidence in others. As for the purpose of this assesment is to know how the muhadatsah and maharah kalam students and what’s the role of learning muhadatsah in arabic study program Unhasy Tebuireng Jombang. This type of research is a qualitative description and use a qualitative approach. This study suggest that muhadatsah at Unhasy Tebuireng Jombang used a methode directly with the instruction manual at Al ‘arabiyyah linnasyi’in juz 3 and expert student Maharah Kalam is about 30% because each generation of graduates and muhadatsah’s learning plays a major role for students to be able to improve their ability to speak well and properly and also increase confidence provide guidance when learning an institution of education.